How to win friends & influence people in the digital age eaudiobook - Dale Carnegie and Associates, Inc (Recorded Books, Inc., 2014)
Dale Carnegie's How to Win Friends & Influence People has sold 15 million copies since its original publication in 1936. Here Carnegie's classic guide on communication and leadership gets a fascinating update for the age of social media. While the digital age may have changed the face of communication, the basic skills necessary for successful social interaction remain as important as ever.